EXPERIMENTAL INVESTIGATION PROPERTIES OF CRUDE & DISTILLED TPO & PPO - Mr. Bhosekar G.S.; Mr. DeshpandeV.V.; Mr. Dimri S.R. (International Journal of Innovations in Engineering Research and Technology, 2021)
Conventional fuels petrochemicals are available in limited sources. And increase in demand of such fuels is extremely high, so it might result in energy crises. So it is our duty to fulfill essential engineering need of society. In order to do that we are finding new economical easily available resources to replace conventional fuel. Plastic is such a material which cannot get destroyed about 400 years, if we burn plastic it may emit hazards gases which are also negatively affect on environment. Similarly waste tire is available in abundant quantity. One of the surveyssays that US alone, over 290 million car tires are discarded annually. Hence we decided to use tire and plastic waste for making alternate fuel.Pyrolysis -The word “Pyrolysis” is originallyobtained from Greek language, Pyro means ‘Fire’ and Lysis means ‘separating’. Pyrolysis is a thermo chemicaldecomposition of organic material at elevated temperatures in the absence of oxygen or any kind of halogen. It involves the simultaneous change ofchemical composition and physical phase, and is irreversible. Pyrolysis is usually the first chemical reaction that occurs in the burning of many solid organic fuels and also of some kinds of plastic.